Mobiles and mobility: The Effect of Mobile Phones on Migration in Niger - Jenny C. Aker; Michael A. Clemens; Christopher Ksoll (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Labor markets in developing countries are subject to a high degree of frictions. We report the results from a randomized evaluation of an adult education program (Project ABC) in Niger, in which students learned how to use simple mobile phones as part of a literacy and numeracy class. Overall, our preliminary results suggest that access to this technology substantially influenced seasonal migration in Niger, increasing the likelihood of migration by at least one household member by 7 percentage points and the number of households' members engaging in seasonal migration. Evidence suggests that there are some heterogeneous impacts of the program, with a higher probability of a household member migrating in one region. These effects do not appear to be driven by differences in observable characteristics of households or differential effects of drought during the survey period. Rather we posit that they are largely explained by the effectiveness of mobile phones as a search technology: Students in ABC villages used mobile phones in more active ways and communicated more with migrants within Niger. These initial results suggest that simple and cheap information technology can be harnessed to affect labor mobility among rural populations.
Keywords: D83; J61; O15; 330